EFFECT OF INCREASING MUSCLE STRENGTH IN ACUTE ISCHEMIC STROKE WITH EARLY PASSIVE EXERCISE IN DR. MOEWARDI SOLO HOSPITAL - Permatasari, Ayu Amalia; Naufal, Adnan Faris; Marinto, Luklu Eko (Universitas Muhammadiyah Surakarta, 2021)
Introduction: Cerebrovascular disease is the second leading cause of death and the third most common cause of disability in the world. In developed countries, one in four men over the age of 85, and one in every five women over the age of 85 have a stroke. Research in Iran shows that 139 out of 100,000 people each year suffer a stroke. Damage to the cerebral can be classified into Ischemic Stroke (IS), which consists of 87% of cases and is caused by thrombotic occlusion of arteries and veins; or Intracerebral Hemorrhagic Strokes (ICHS), which comprise 13% of cases and are caused by rupture of blood vessels by hypertension or aneurysms, trauma, and translucent brain injury. Ischemic stroke is the death of brain tissue due to impaired blood flow to the brain, caused by clogged cerebral or cervikal arteries. Case Presentation: 72 year-old female office came to the hospital with complaints of difficulty moving the left side of her limbs, difficulty speaking, and the condition was so weak that it was difficult to respond. She is being hospitalized about 7 days and her condition still weak and hard to response. Management and Outcome: This therapy is carried out 3 times with a duration of exercise of 20 minutes. Muscle strength examination in acute stroke cases is measured using the Oxford Scale and level of neurological deficits measured using National Institute of Health Stroke Scale (NIHSS). Discussion: Muscle strength is strongly related to the neuromuscular system which is how much the nervous system can activate muscles to contract, so the more muscle fibers are activated, the greater the strength that the muscles produce. Thus, the more muscle fibers are activated, the greater the force produced by the muscles. In addition, the benefits of early passive exercise in stroke patients can also increase or maintain flexibility and muscle stiffness, maintain heart and respiratory function, prevent stiffness in joints, stimulate blood circulation, and prevent deformities, stiffness and contracture. Conclusion: physiotherapy program in acute stroke cases who are still hospitalized three times using Early Passive Exercise can increased muscle strength, and for neurological deficits still in the very heavy category. This therapy is advised to continue to be done in order to achieve the goal of patient recovery.